حكم آلات الملاهي عند جمعية نهضة العلماء وجمعية المحمدية بإندونيسيا: دراسة فقهية مقارنة: The Ruling on Musical Instruments According to Nahdlatul Ulama and Muhammadiyah in Indonesia: A Comparative Jurisprudential Study - Usamah Maming Gappa; Ibrahim Rasheed Saad Al-Shubrumi (البصيرة: مجلة الدراسات الإسلامية, 2025)
This study aims to explain the ruling on musical instruments according to Nahdlatul Ulama (NU) and Muhammadiyah in Indonesia by comparing their views with those of scholars from the four major Islamic legal schools. It also discusses the reasons behind their differences, identifies the stronger opinion (rājih), and examines the methodology used by both organizations in addressing and determining legal rulings. The study further compares these methodologies with those employed by classical jurists. The researcher adopts three approaches: an inductive approach to compile the disputed issues between the two organizations, an analytical approach to examine and analyze those issues, and a deductive approach to explore the methods used in determining legal rulings. The study finds that the two organizations differ in their general views on musical instruments (al-maʿāzif), resulting in two primary opinions: prohibition (ḥarām) and permissibility (mubāḥ). This divergence stems from their differing reliance on the principle of original permissibility and their evaluation of the authenticity of hadiths that prohibit musical instruments. Those who consider the prohibition hadiths as strong argue that musical instruments are forbidden, while those who weaken these hadiths—even if narrated in Ṣaḥīḥ al-Bukhārī—base their position on the original principle of permissibility.